The actor's book of monologues for women from non-dramatic sources - Rudnicki, Stefan, 1945- (New York, N.Y., U.S.A. : Penguin Books, 1991)
Collection of over 200 monologues for women drawn from non-dramatic sources including poetry, fiction, diaries, journals, and public documents.
Includes bibliographical references (p. 331-333).
Adult
Keywords: Acting; Monologues; Women -- Literary collections